2002
DOI: 10.1103/physrevc.65.032801
|View full text |Cite
|
Sign up to set email alerts
|

Astrophysically important26Sistates studied with the28Si

Abstract: The production of the 26 Al radioisotope in astrophysical environments is not understood, in part, because of large uncertainties in key nuclear reaction rates. The 25 Al(p,␥) 26 Si reaction is one of the most important, but its rate is very uncertain as a result of the lack of information on the 26 Si level structure above the proton threshold. To reduce these uncertainties, we have measured differential cross sections for the 28 Si(p,t) 26 Si reaction and determined excitation energies for states in 26 Si. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
192
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(205 citation statements)
references
References 13 publications
13
192
0
Order By: Relevance
“…Gamma-decay studies of 26 Si performed at Gammasphere [54,60] have shown that there is a 4 + state at 5517.0 keV, a 1 + level at 5675.9 keV and a 0 + state at 5890.1 keV. A 3 + state at 5928.7 keV has been confirmed via beta-decay studies of 26 P [51,58] and it is also supported by [50,53,56]. The spin for the next excited state at 5946 keV is unclear.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Gamma-decay studies of 26 Si performed at Gammasphere [54,60] have shown that there is a 4 + state at 5517.0 keV, a 1 + level at 5675.9 keV and a 0 + state at 5890.1 keV. A 3 + state at 5928.7 keV has been confirmed via beta-decay studies of 26 P [51,58] and it is also supported by [50,53,56]. The spin for the next excited state at 5946 keV is unclear.…”
Section: Discussionmentioning
confidence: 61%
“…The knowledge of these states has improved considerably thanks to several measurements on the excited levels of 26 Si [49][50][51][52][53][54][55][56][57][58][59][60][61]. Gamma-decay studies of 26 Si performed at Gammasphere [54,60] have shown that there is a 4 + state at 5517.0 keV, a 1 + level at 5675.9 keV and a 0 + state at 5890.1 keV.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease in the abundance of 30 P consequently reduces that of 30 Si produced from 30 P(β + ) 30 Si. The rate of the 30 P(p, γ) 31 S reaction has been evaluated in Refs. [8,67,68] and more recently in Ref.…”
Section: B Resultsmentioning
confidence: 99%
“…In § I, it was emphasized that 29,30 P(p, γ) 30,31 S are the two reactions that are thought to affect the silicon isotopic ratios in nova ejecta.…”
Section: Nova Isotopic Abundancesmentioning
confidence: 99%
“…Since a direct measurement of the 25 Al(p,γ) 26 Si reaction is presently untenable due to insufficiently intense beams of 25 Al, transfer reactions and in-beam gamma-ray spectroscopic studies have been used extensively to determine indirectly the important level properties of 26 Si, such as resonance energies and spin-parity assignments [1,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. The rate has been re-evaluated recently [23,[26][27][28], and Ref.…”
Section: Introductionmentioning
confidence: 99%